Case Report: A de novo NLRP3 variant resulting in autoinflammatory disease in a Chinese newborn - Xie, Mingyu; Wan, Jingjing; Zheng, Xin; Zou, Xian; Chen, Wanting; Zhang, Kanglin; Yuan, Huiting; Zhang, Zhenhong; Zeng, Haisheng (Frontiers in Immunology, 2023)
Background: Cryopyrin-associated periodic syndromes (CAPS) have been considered autoinflammatory diseases resulting from NLRP3 gene mutations. In recent years, these conditions have been redefined as NLRP3-associated autoinflammatory diseases (NLRP3-AID). Our previous study highlighted a case of a Chinese individual carrying the de novo NLRP3 mutation. Results: A female child carrying a de novo variant (c.1718T ＞ G, p. L573W) in the NLRP3 gene was presented in this work. The patient manifested various symptoms, including recurrent fever, a rash resembling urticaria, arthritis, physical growth retardation, a notable prominence of the forehead, and a flat nose bridge. Additionally, inflammatory markers, like WBC count, PLT count, CRP, ESR, and IL-6 showed elevated levels. Additionally, we observed interstitial pulmonary disease in the patient, which is not frequently mentioned in previous studies. Notably, the proband did not present with any ocular, auditory, or neurological symptoms. After 12 weeks of subcutaneous canakinumab injection, there was a clear improvement in the patient's clinical manifestations and inflammatory markers.Conclusions: Our study contributes to broadening the clinical spectrum of established pathogenic variants of NLRP3 gene, which are related to NLRP3-AID.